The indigenous cattle of Mozambique - Alberro, M. (1983)
Animal genetic resources conservation and management depend on national identification of the indigenous adapted breeds of cattle. This paper describes the indigenous cattle breeds of Mozambique. Detailed descriptions of their habitat and husbandry methods, breed characteristics and population included.